REORMULASI KEBIJAKAN HUKUM PIDANA TERHADAP PEMBERIAN SANKSI PIDANA BERSYARAT - Lia Khetryn Sinaga; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In criminal law, there are conditional penalties. Conditional or probationary punishment (parole voorwaardelijke veroordeling) as regulated in Articles 14a-14f of the Criminal Code. In fact, many cases have been sentenced to conditional criminal penalties, which upon further examination do not match the resulting consequences. It is still far away from the implementation of the law and as expected it is because there are still obstacles and challenges in the material of law, legal apparatus, facilities and infrastructure as well as other factors that influence it. The purpose of writing this thesis, namely: First, to find out the arrangements for the provision of conditional criminal sanctions in Indonesian criminal law, Second, to find out the reformulation of criminal law policies towards the impending conditional criminal sanctions in the future.This research is classified in this type of research as normative legal research or it can be called doctrinal legal research. Normative legal research is literature law research. In this normative research, the writer conducts research on legal principles. Research on legal principles is research carried out on legal principles which are benchmarks for behaving or having an appropriate or inappropriate attitude. This research is descriptive analysis, which describes and analyzes the problems raised which aims to describe concretely about the reformulation of criminal law policies against conditional criminal sanctions.From the results of the research and discussion, it can be concluded that, first, in the regulation there are no restrictions on the imposition of conditional and generalizing crimes whether serious or minor crimes as long as the sanctions imposed are not more than one year; second, there has been no effort to reform criminal law, namely to create a codification of criminal law in conditional criminal arrangements with the application of sanctions that only apply to minor crimes.Keywords : Reformulation-Criminal Law Policy-Conditional Criminal